Readiness and Needs for Professional Development of Vocational School Teachers in Implementing Link and Match in The Industry 4.0 Era - Fadhillah, Lola; Arifin, Zainal; Hernawan, Asep Herry (Indonesian Journal of Education and Mathematical Science, 2026)
The high rate of open unemployment among vocational school graduates shows that their skills don't fully match industry needs, especially in the Industry 4.0 era, which demands an adaptive, digitally literate, and vocationally skilled workforce. This condition emphasizes the importance of teacher readiness and professionalism as the key to the successful implementation of link and match so that learning is relevant to the demands of the business and industrial world (DUDI). This study aims to analyze the readiness of vocational school teachers and the need for professional development in North Sumatra by comparing teachers in urban and rural areas. The study uses a qualitative descriptive approach with written interviews. Participants consisted of four productive teachers from schools in Medan City and six teachers from one rural school. The interview instrument explored understanding of link and match, pedagogical readiness, digital competence, vocational skills, collaboration with DUDI, obstacles, and training needs. Data were analyzed using Elo and Kyngäs content analysis. The results showed that urban teachers were more prepared in terms of implementation due to the support of facilities, technology, and access to industry training, while rural teachers were more prepared conceptually but were hampered by limited facilities and access to industry. Both had similar needs regarding vocational training, digital technology, and industry-based programs. The findings emphasized the need for context-based professional development to strengthen the role of teachers in preparing graduates who are relevant to industry needs.